2018
DOI: 10.3390/su10051634
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Barriers for Water Co-Governance—A Critical Analysis of Seven Cases of Diffuse Water Pollution from Agriculture in Europe, Australia and North America

Abstract: Diffuse Water Pollution from Agriculture (DWPA) and its governance has received increased attention as a policy concern across the globe. Mitigation of DWPA is a complex problem that requires a mix of policy instruments and a multi-agency, broad societal response. In this paper, opportunities and barriers for developing co-governance, defined as collaborative societal involvement in the functions of government, and its suitability for mitigation of DWPA are reviewed using seven case studies in Europe (Poland, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 49 publications
(63 reference statements)
1
32
0
Order By: Relevance
“…In general, studies conducted in England concluded that in spite of attempts to try different and more bottom-up approaches, participatory experiences have been highly variable [97] and, further, this potential had not been fully exploited [43,74,98,99]. In addition, since 2013, the UK Government has attempted a Catchment Based Approach (CaBA) to foster active stakeholder engagement and to strengthen existing and newly formed catchment partnerships [100]. However, the CaBA did not replaced public participation practices under the WFD and this policy disconnect still remains to be addressed [43].…”
Section: Implementation Of the Wfd In The Case Settingsmentioning
confidence: 99%
“…In general, studies conducted in England concluded that in spite of attempts to try different and more bottom-up approaches, participatory experiences have been highly variable [97] and, further, this potential had not been fully exploited [43,74,98,99]. In addition, since 2013, the UK Government has attempted a Catchment Based Approach (CaBA) to foster active stakeholder engagement and to strengthen existing and newly formed catchment partnerships [100]. However, the CaBA did not replaced public participation practices under the WFD and this policy disconnect still remains to be addressed [43].…”
Section: Implementation Of the Wfd In The Case Settingsmentioning
confidence: 99%
“…The starting point for identifying appropriate governance instruments is the understanding of the problem at hand [20,21]. Research often understands diffuse (nitrate) pollution of freshwater as a wicked or complex problem [13,15,22]. Of particular importance is the role of conflicting interests between stakeholders and policies, hinting at the nexus dimension of the problem.…”
Section: The Complexity Of the Problemmentioning
confidence: 99%
“…While governments have traditionally focused on coercion, the current debate on diffuse pollution has revolved around hybridity and, thus, the right mix of the governance instruments. Based on this literature, a synergistic mix is generally desirable, given different benefits of instruments [11,15,16]. Most prominently, current advisory, or information strategies need to be expanded with measures such as tailor-made incentives [31][32][33].…”
Section: Assumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coefficients in columns (2), (3), (5), and (6) are significantly negative, and the absolute values of coefficient in type-I counties are smaller than those in type-B counties, indicating that as water polluting regulation got stricter, production activities by new polluting enterprises in type-I and type-B counties decreased; while within the same prefecture-level city, county B is located upstream of the river in county I. To prevent upstream pollution, lower the aggregation effect of monitoring data of water pollution and fulfill the environmental requirements set up by central government, local governments stopped new water polluting enterprises from establishing factories in upstream regions [37]. From the spatial difference of new enterprise locations, it could be seen that for water polluting enterprises, counties with relatively lax regulation (the most downstream counties of prefecture-level cities) are more attractive, reflecting the strategic allocating of the government for water polluting enterprises.…”
Section: Identifying the Relationship Between Regulation And Pollutinmentioning
confidence: 99%